Consensus on the management of patients with psoriatic arthritis in a dermatology setting. (11th January 2018) - Gisondi, P.; Altomare, G.; Ayala, F.; Conti, A.; Dapavo, P.; De Simone, C.; Foti, C.; Idolazzi, L.; Lubrano, E.; Malara, G.; Marchesoni, A.; Olivieri, I.; et al.
Abstract: Background: Psoriatic arthritis (PsA) is a chronic inflammatory disease associated with psoriasis (PsO). Early diagnosis and prompt therapeutic intervention are crucial for limiting PsA progression and prevention of disability. Dermatologists are in a privileged position to detect early PsA. The management of patients with PsA in the dermatology setting is widely variable. Objective: To provide practical recommendations for the management of patients with PsA in the dermatology setting including early diagnosis and treatment. Methods: A consensus document was written by an expert panel composed by dermatologists ( n = 12) and rheumatologists ( n = 6). Eleven highly relevant questions were selected and elaborated with answers/statements based on a narrative literature review. The resulting document was discussed in a face‐to‐face meeting adopting a nominal group technique to reach consensus (i.e. 100% agreement) using the Delphi method. Results: A consensus was achieved in defining the following: the clinical characteristics differentiating inflammatory and non‐inflammatory signs and symptoms of joint disease; the most important differential diagnoses of PsA in clinical practice; the most useful screening questionnaires, serum laboratory tests and imaging techniques for the detection of early PsA; the criteria for dermatologist to refer patients with PsO to rheumatologist; the criteria for the diagnosis of PsA; the selection of the indices that the dermatologist could use for measuring the activity and severity of PsA in clinical practice; when systemic steroids and/or intra‐articular steroid injections are indicated in the treatment of PsA. Finally, systemic treatments including synthetic and biologic disease‐modifying antirheumatic drugs to be considered for the treatment of PsA have been reported. Conclusions: The implementations of these practical recommendations could be very helpful for the management of patients with PsA in the dermatology setting including early diagnosis and treatment.